2015
DOI: 10.1016/j.apjtm.2015.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics for characterization of gender differences in patients infected with dengue virus

Abstract: The (1)H NMR metabolomic investigation combined with appropriate algorithms and pattern recognition procedures, gave an evidence for the existence of distinct metabolic differentiation of individuals, according to their gender, modulates with the infection risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Nevertheless, altered lipid metabolism is not unique to CMV infection. Hepatitis C virus (HCV) , human immunodeficiency virus (HIV) , and dengue virus are also associated with dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, altered lipid metabolism is not unique to CMV infection. Hepatitis C virus (HCV) , human immunodeficiency virus (HIV) , and dengue virus are also associated with dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%
“…Different responses to the four serotypes were observed, which could be related to the broad range of manifestations and different DENV infection outcomes observed in the clinical setting. In addition, it was recently shown that gender discriminates the urine metabolic profile in subjects with DENV infection, and, like the in vitro study, changes in the levels of TCA cycle intermediates and amino acids contributed to the discrimination of groups according to infection outcomes (19).…”
mentioning
confidence: 99%
“…As described in our previous article (Shahfiza et al, 2015), 1 H NMR spectra of the urine samples from both infected and healthy individuals were acquired with AVANCE III 500 MHz Bruker spectrometer with BBO broadband probe using TSP (δ 0.00 ppm) as an internal standard and D 2 O as the frequency lock at 300 K.…”
Section: Equipmentmentioning
confidence: 99%
“…Biological samples. Sample size was calculated using Sample Size Program (http//www.kck.usm.my/ppsg/ stats_resources.htm), while in clusion an dexclusion criteria were considered as described by Shahfiza et al, (2015).…”
Section: Equipmentmentioning
confidence: 99%
See 1 more Smart Citation